2020
DOI: 10.3390/vaccines8040586
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Development of New Vaccines for Tuberculosis

Abstract: Currently, there is only one licensed vaccine against tuberculosis (TB), the Bacillus Calmette–Guérin (BCG). Despite its protective efficacy against TB in children, BCG has failed to protect adults against pulmonary TB, lacks therapeutic value, and causes complications in immunocompromised individuals. Furthermore, it compromises the use of antigens present in the purified protein derivate of Mycobacterium tuberculosis in the diagnosis of TB. Many approaches, e.g., whole-cell organisms, subunit, and recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 78 publications
1
33
0
Order By: Relevance
“…Various of them are being in BCG, too, cause antigenic cross-reactivity and inducing a high degree of false positivity (Kasempimolporn et al 2019 ). A reduction in the antigen cross-reactivity is needed for test precision, despite the limited investigation and discussions that have marked this dilemma (Whitlow et al 2020 ).…”
Section: Exosomal Rnas As a Diagnostic And Therapeutic Biomarker For Tuberculosismentioning
confidence: 99%
“…Various of them are being in BCG, too, cause antigenic cross-reactivity and inducing a high degree of false positivity (Kasempimolporn et al 2019 ). A reduction in the antigen cross-reactivity is needed for test precision, despite the limited investigation and discussions that have marked this dilemma (Whitlow et al 2020 ).…”
Section: Exosomal Rnas As a Diagnostic And Therapeutic Biomarker For Tuberculosismentioning
confidence: 99%
“…Two other subunit vaccine candidates which have undergone clinical trials in humans are H1:IC31 and H56:IC31 [ 190 , 191 ]. The subunit vaccine H1:IC31 contains a fusion of Ag85B and ESAT6 and is given along with the adjuvant IC31 [ 192 , 193 ].…”
Section: Rd1 Genes and Encoded Proteinsmentioning
confidence: 99%
“…A phase 1b randomized study with the H56:IC31 vaccine showed that the vaccine had acceptable safety profiles in M. tuberculosis -uninfected adults and induced immunizing antigen-specific cellular and humoral immune responses [ 204 ]. This vaccine candidate is now being tested in phase 2a clinical trials, and recruitment has started for the phase 2b clinical trial [ 190 ].…”
Section: Rd1 Genes and Encoded Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The view that adequate protection against bacterial infections such as TB will require delivery of a complexity of diverse antigens by virulence-attenuated vectors such as live BCG or attenuated M. tuberculosis has not been discounted; current understanding of the requirements for generating protective immunity is limited [ 9 ] and multiple forms of vaccine are being investigated [ 10 ], and must continue to be investigated. However, the attainment of potent protection with a limited number of TB antigens (subunits) remains a realistic ambition that has precedents in animal models of TB [ 11 , 12 ] and a range of subunit candidate vaccines are in clinical trials [ 9 , 10 ]. The ivt RNA approach may be ideally suited for the subunit approach.…”
mentioning
confidence: 99%